Terapia no farmacológica en cuidados paliativos de pacientes con cáncer de mama - Molina Salcedo, Arianna Lilibeth (2025)
Background: Non-pharmacological therapy in palliative care of patients with breast cancer plays a fundamental role in improving the quality of life of patients, through comprehensive approaches that relieve physical, emotional, and spiritual suffering. Objective: To evaluate the effectiveness of non-pharmacological therapies in the palliative care of patients with breast cancer, through a systematic review. Methodology: This systematic review is a descriptive and transversal narrative study, with a qualitative approach, following the PRISMA protocol. The systematic search was carried out using the PICO structured question-based strategy. Articles published in English and Spanish in the last 5 years in Pubmed, Web of Science and Scopus were included. In addition, the Degrees of Recommendation, Assessment, Development and Evaluation (GRADE) were used. Results: The studies combine cancer registries, systematic reviews with clinical trials and longitudinal analyses. Cognitive-behavioral therapy, mindfulness, acupuncture, physical activity, and therapeutic compresses improved different types of fatigue and pain in several studies. On the other hand, reflexology and short-term exercise programs were not consistently effective. Psychological therapies, exercise and some complementary treatments improve the quality of life and reduce anxiety and depression in patients with advanced cancer. Palliative radiotherapy did not impact survival, and some interventions, such as guarana and body vibration, showed no significant benefits. Conclusions: Non-pharmacological and palliative therapies are effective and safe in patients with breast cancer.